PERLINDUNGAN HUKUM BAGI JAMAAH HAJI DAN UMROH DALAM PERJANJIAN PERJALANAN IBADAH MELALUI PT. ZAFA MULIA MANDIRI (STUDI PADA CABANG KETIGA ZAFA TOUR PT. ZAFA MULIA MANDIRI) - Segara, Andika; Cholidi, Cholidi; Erniwati, Erniwati (Program Studi Muamalah Fakultas Syariah dan Hukum, 2020)
Legal Protection for Hajj and Umrah Pilgrims in the Worship Travel Agreement through PT. Zafa Mulia Mandiri (Study at the Third Branch of Zafa Tour PT. Zafa Mulia Mandiri). In this case, it is undeniable that in Indonesia, there has been a lot of neglect of the congregation, the absence of the congregation, and other fraud committed by the bureau that organizes the Umrah worship. So this study aims to review legal protection and responsibility for Haj and Umrah pilgrims by Zafa Tour PT. Zafa Mulia Mandiri. The focus of this research is legal protection. This type of research is field research. The data sources of this research are primary data and secondary data. Data collection techniques used in this study, namely observation, interview, and documentation. This research data analysis technique used qualitative research with qualitative descriptive method. The results showed that (1) Mechanism of Legal Protection Agreement for Hajj and Umrah Pilgrims at PT. Zafa Mulia Mandiri. The validity of the agreement between the Zafa Tour and the congregation after the DP and repayment made by the congregation according to the departure schedule he chose. (2) In the Sharia Economic Law Review on Legal Protection for Hajj and Umrah Pilgrims of PT. Zafa Mulia Mandiri is in accordance with the laws of Hifdz Diin (safeguarding religion) and Hifdz Nafs (guarding the soul) of sya'rah, where the settlement is by deliberation, does not harm one another and is in accordance with the provisions of the Laws and Regulations of the Minister of Religion of the Republic of Indonesia